Systematic review of drug effects in humans and models with surfactant-processing disease. (11th July 2018) - Klay, Dymph; Hoffman, Thijs W.; Harmsze, Ankie M.; Grutters, Jan C.; van Moorsel, Coline H.M.
Fibrotic interstitial pneumonias are a group of rare diseases characterised by distortion of lung interstitium. Patients with mutations in surfactant-processing genes, such as surfactant protein C ( SFTPC ), surfactant protein A1 and A2 ( SFTPA1 and A2 ), ATP binding cassette A3 ( ABCA3 ) and Hermansky–Pudlak syndrome ( HPS1, 2 and 4 ), develop progressive pulmonary fibrosis, often culminating in fatal respiratory insufficiency. Although many mutations have been described, little is known about the optimal treatment strategy for fibrotic interstitial pneumonia patients with surfactant-processing mutations. We performed a systematic literature review of studies that described a drug effect in patients, cell or mouse models with a surfactant-processing mutation. In total, 73 articles were selected, consisting of 55 interstitial lung disease case reports/series, two clinical trials and 16 cell or mouse studies. Clinical effect parameters included lung function, radiological characteristics and clinical symptoms, while experimental outcome parameters included chemokine/cytokine expression, surfactant trafficking, necrosis and apoptosis. SP600125, a c-jun N-terminal kinase (JNK) inhibitor, hydroxychloroquine and 4-phenylbutyric acid were most frequently studied in disease models and lead to variable outcomes, suggesting that outcome is mutation dependent. This systematic review summarises effect parameters for future studies on surfactant-processing disorders in disease models and provides directions for future trials in affected patients. Drug effects in disease models of surfactant-processing disease are highly dependent on mutation http://ow.ly/ZYZH30k3RkK